Leksykalne środki wartościujące i ich tekstowo-podmiotowe uwarunkowania w dyskursie wspomnieniowym powstańców warszawskich (na wybranych przykładach z Archiwum Historii Mówionej Muzeum Powstania Warszawskiego) - Duda, Beata; Ficek, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The subject of the article is the description of selected lexical determinants of evaluation and the determination of these elements’ significance in the memoir discourse of the Warsaw insurgents, more precisely: in statements regarding the meaning of the uprising’s outbreak. The evaluative lexis has also been considered in view of textual mechanisms and with reference to the evaluative subject. The research material consists of approximately 3,400 transcripts of interviews from the Oral History Archive of the Warsaw Uprising Museum. Additionally, the desire to broaden the thought on oral history texts to date with a linguistic perspective prompted the authors to use the assumptions and findings of memory linguistics, axiolinguistics and corpus linguistics in their considerations. Analyses of the indicated problem (both quantitative and qualitative ones) allow for drawing the following final conclusions: the lexical determinants of evaluation richly represented in autobiographical narratives and the textual and subjective references thereof are subordinate to the persuasive function manifested in the public debate in the context of the dispute about the sense of the uprising; they also prove the polarization of the opinions of the insurgents multifacetedly evaluating the events of 1944, either positively or negatively, and sometimes taking military action despite their personal opinion.